Changing Technologies of RNA Sequencing and Their Applications in Clinical Oncology - Wang, Ye; Mashock, Michael; Tong, Zhuang; Mu, Xiaofeng; Chen, Hong; Zhou, Xin; Zhang, Hong; Zhao, Gexin; Liu, Bin; Li, Xinmin (Frontiers in Oncology, 2020)
RNA sequencing (RNAseq) is one of the most commonly used techniques in life sciences, and has been widely used in cancer research, drug development, and cancer diagnosis and prognosis. Driven by various biological and technical questions, the techniques of RNAseq have changed rapidly from bulk RNAseq, laser-captured micro-dissected RNAseq, and single-cell RNAseq to digital spatial RNA profiling, spatial transcriptomics, and direct in situ sequencing. These different technologies have their unique strengths weaknesses, and suitable applications in clinical oncology. To guide cancer researchers to select the most appropriate RNAseq technique for their biological questions, we will discuss each of their technologies, technical features and clinical applications in cancer. We will also clearly state the driving force of the technological change underlying biological and technical reasons to facilitate cancer researchers to capture the key differences of these technologies and their applications.